DEFORESTATION AND ITS IMPLICATIONS TO THE POPULATION OF SUMATRAN TIGER (PANTHERA TIGRIS SUMATRAE) IN BUKIT BARISAN SELATAN NATIONAL PARK, SUMATRA - Suyadi, Suyadi (GEOMATIKA, 2011)
Bukit Barisan Selatan National Park (BBSNP) is home for Sumatran tigers (Panthera tigris sumatrae), one of worldâs most endangered mammals (Appendix I of CITES). Much of the forest cover in BBSNP has been cleared dramatically and deforestation is a great threat on the population of tigers. Remotely-sensed data sets were linked with wildlife survey using camera traps to examine the deforestation from 1998 to 2006 and its effects to the population of Sumatran tigers in BBSNP. This paper assesses the relationship between deforestation in BBSNP with the population of Sumatran Tigers. It was found that the average rates of forest loss in BBSNP were 18.76 km2 per year, representing a 7% loss from 1998 to 2006. In addition, the number of tigers declined from 57 tigers in 2000 to 22 tigers in 2006, and tiger density decrease from 2.25 tigers/100km2 in 2000 to 1.16 tiger/100km2 in 2006. Keywords: Deforestation, Sumatran tiger, satellite imageries, Camera Trap, Bukit Barisan Selatan National Park.Â ABSTRAKTaman Nasional Bukit Barisan Selatan adalah habitat bagi harimau Sumatra (Panthera tigris sumatrae), salah satu mamalia yang terancam keberadaannya (Lampiran I CITES). Banyak hutan yang sudah dibabat secara dramatis dan penggundulan hutan merupakan ancaman yang besar pada populasi harimau. Data penginderaan jauh dikorelasikan dengan survei satwa liar yang menggunakan camera traps untuk mengkaji deforestasi dari tahun 1998 sampai 2006 dan pengaruhnya pada populasi harimau Sumatra dalam wilayah taman nasional tersebut. Makalah ini mengkaji hubungan antara penurunan jumlah hutan dengan populasi harimau Sumatra. Ditemukan bahwa rata-rata kehilangan hutan di taman nasional ini adalah 18,76 km per tahun, sekitar 7% dari tahun 1998 s.d. 2006. Jumlah harimau yang terekam menurun dari 57 di tahun 2000 menjadi 22 tahun 2006, dan populasinya menurun dari 2,25/100km2 di tahun 2000 menjadi 1,16/100km2 tahun 2006. Katakunci: Penggundulan hutan, harimau Sumatra, citra satelit, kamera trap,Taman Nasional Bukit Barisan Selatan.